KETERSEDIAAN INPUT DARI LINGKUNGAN PADA AGROBISNIS BUDIDAYA IKAN TOMAN DALAM KARAMBA DI KABUPATEN HULU SUNGAI UTARA - Irma Febrianty; Rina Mustika (Universitas Lambung Mangkurat, 2021)
The availability of inputs is very decisive in the sustainability of the Toman fish farming business in karamba where the availability of the necessary inputs must be available continuously, both investment and operational. The problem faced by cultivators is the lack of seed availability for cultivation and the difficulty of obtaining fish feed in the form of small fish and small shrimp. This study used a survey method at a purposive research location in Hulu Sungai Utara Regency. Results of the study: 1. The availability of inputs and infrastructure for toman fish cultivation in karamba, was fulfilled from HSU Regency in South Kalimantan Province and East Kalimantan and Central Kalimantan. 2. Supporting facilities for Toman fish cultivation in karamba that can be accessed by Toman fish cultivators are counseling on the technicalities of toman fish cultivation by the government and higher education institutions (Faculty of Fisheries and Marine Affairs, ULM), as well as seed assistance from the government.